Caracterização clínica, demográfica e nutricional de pacientes oncológicos atendidos em um hospital público - 2008 - Prado, Corina Dias do [UNESP]; Campos, Juliana Alvares Duarte Bonini [UNESP] (My University, 2011)
To identify the clinical and sociodemographic characteristics and the nutritional status of patients with cancer. A cross-sectional study with non-probability sample design was performed. One hundred and thirty-four adults with cancer, interned at Amaral Carvalho Hospital (Jaú- SP) between April and November 2008, participated in this study. Clinical and sociodemographic data of the sample were obtained. The Patient-Generated Subjective Global Assessment was used to identify the nutritional status. Descriptive statistics and chi-square test (χ2 ) was used. The mean age of patients was 51.13±9.59 years. Most of the patients presented gastrointestinal and head and neck cancer in clinical stages III and IV, and were mainly treated with chemotherapy. Between the participants 73,88% were of the masculine sex, 65,67% were married and 65,68% presented education level below the gymnasial complete. Sixty-fi ve (48.51%) patients were classifi ed as “well-nourished”, 56 (41.79%) as “moderately malnourished (or suspected)”, and 13 (9.70%) as “severely malnourished”. There was no signifi cant association between the nutritional status and the sociodemographic characteristics and the antineoplastic treatment. The malnourished patients presented a higher frequency of eating disorders (p=0.001), lack of appetite (p=0.001), nausea (p=0.018), vomiting (p=0.021), pain (p=0.010), strange taste (p=0.001) and nausea at the smell of food (p=0.018) than the well-nourished ones. There was a high prevalence malnutrition signifi cantly associated with the presence of clinical symptoms.

Identifi car as características clínicas, sóciodemográfi cas e o estado nutricional de pacientes oncoló- gicos. Estudo transversal com delineamento amostral não probabilístico. Participaram 134 pacientes oncológicos adultos, internados no Hospital Amaral Carvalho (Jaú-SP) de abril a novembro de 2008. Foram levantadas informa- ções para caracterização clínica e sócio-demográfi ca da amostra. Para identifi cação do estado nutricional aplicouse a Avaliação Subjetiva Global – Produzida pelo Paciente. Utilizou-se estatística descritiva e o teste de qui-quadrado (χ2 ). A média de idade dos pacientes foi 51,13±9,59 anos. Observou-se predominância do câncer gastrointestinal e de cabeça e pescoço, estádio clínico III e IV sendo a quimioterapia tratamento mais comum. Dos participantes 73,88% eram do sexo masculino, 65,67% eram casados e 65,68% apresentavam nível de escolaridade abaixo do ginasial completo. Dos pacientes, 65 (48,51%) foram classifi cados como ”bem nutrido”, 56 (41,79%) “moderadamente desnutridos (ou suspeita)” e 13 (9,70%) “gravemente desnutridos”. A associação do estado nutricional com as características sócio-demográfi cas e tratamento antineoplásico foi não signifi cativa. Os indivíduos desnutridos apresentaram problema para se alimentar (p=0,001), ausência do apetite (p=0,001), náuseas (p=0,018), vômitos (p=0,021), dor (p=0,010), gosto estranho (p=0,001) e enjôo ao cheiro dos alimentos (p=0,018) com maior frequência que os eutrófi - cos. Observou-se grande prevalência de desnutrição sendo esta signifi cativamente associada à presença de sintomas clínicos.
Clinical, demographic and nutritional characterization of patients with cancer assisted at a public hospital – 2008
Keywords: Neoplasms; Neoplasm staging; Nutritional assessment; Malnutrition; Neoplasias; Estadiamento de neoplasias; Avaliação nutricional; Desnutrição